Implementation of Data Communication between CS3000 and SIEMENS PLC Subsystem - PANG Xiao-xia; WANG Sheng (Gong kuang zi dong hua = Industry and mine automation, 2011)
In view of problems of adding cost and going against integrated monitoring and control for technological process and information collection of all devices because monitoring and control for each section of mineral seperation plant is realized by adding remote I/O station or setting individual control room, the paper proposed a scheme of using Profibus-DP protocol to realize data communication between CS3000 and SIEMENS PLC subsystem. Taking ALP111 communication module of CS3000 as example, it introduced configurations of hardware and software of the scheme. The actual application showed that the scheme realizes reliable data communication between CS3000 master and SIEMENS PLC subsystem with good effect of field monitoring and control.